Processing by rhomboid protease is required for Providencia stuartii TatA to interact with TatC and to form functional homo-oligomeric complexes - Fritsch, M; Krehenbrink, M; Tarry, M; Berks, B; Palmer, T (2012)
The twin arginine transport (Tat) system transports folded proteins across the prokaryotic cytoplasmic membrane and the plant thylakoid membrane. In Escherichia coli three membrane proteins, TatA, TatB and TatC, are essential components of the machinery. TatA from Providencia stuartii is homologous to E. coli TatA but is synthesized as an inactive pre-protein with an N-terminal extension of eight amino acids. Removal of this extension by the rhomboid protease AarA is required to activate P. stuartii TatA. Here we show that P. stuartii TatA can functionally substitute for E. coli TatA provided that the E. coli homologue of AarA, GlpG, is present. The oligomerization state of the P. stuartii TatA pro-protein was compared with that of the proteolytically activated protein and with E. coli TatA. The pro-protein still formed small homooligomers but cannot form large TatBC-dependent assemblies. In the absence of TatB, E. coli TatA or the processed form of P. stuartii TatA form a complex with TatC. However, this complex is not observed with the pro-form of P. stuartii TatA. Taken together our results suggest that the P. stuartii TatA pro-protein is inactive because it is unable to interact with TatC and cannot form the large TatA complexes required for transport. © 2012 Blackwell Publishing Ltd.